MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KETERAMPILAN KREATIVITAS ILMIAH SISWA - Yuni Dyah Pratiwi; Albertus Djoko Lesmono; Sri Astutik (FKIP Universitas Jember, 2018)
Creative Problem Solving is a learning model which gives the opportunity to students constructing concepts, discussing materials, issuing opinions, and developing creativity in learning group. The purpose of this research was understand the improvement of concepts comprehension and scientific creativity skill of students on Elasticity and Hooke's law. This research was included in descriptive. This research was carried out based on the school availability as a place of research,. Research respondent in this case is Man 1 JEMBER in Science Class. Furthermore, sampling technique in this study was based on purposive sampling area. Collecting data method used pre-test and post-test. In this research, the instrument was essay test, consisted of nine item of concept comprehension and seven item of scientific creativity. The data analysis method of concept comprehension and seven item of scientific creativity used Normalized Gain (Ng). Based on this study, the concept comprehension of students significantly increased to 0,71 (high) while the scientific creativity skill increased to 0.4 (medium).Keyword: CPS, Concept Comprehension, Scientific Creativity Skill